The Influence of Environmental Performance, Carbon Emissions Disclosure, Green Process Innovation, and Green Product Innovation on Firm Value in the Food and Beverage Sub-sector - Prasetyo, Putra Rizky; Suryaningsum, Sri (Dinasti Publisher, 2026)
This study aims to empirically examine the effect of environmental performance, carbon emissions disclosure, green process innovation, and green product innovation on firm value in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. This research employs a quantitative approach using a causal associative design, using secondary data from annual and sustainability reports of companies. The sample was selected using purposive sampling, resulting in 149 observations, and analyzed using multiple linear regression with SPSS version 26. The results show that environmental performance has a negative and significant effect on firm value, indicating that higher PROPER ratings are not always perceived positively and may be viewed as a cost burden by investors. Carbon emissions disclosure also has a negative and significant effect, indicating that transparency in carbon emissions is still viewed as a signal of risk and potential future costs. Meanwhile, green process innovation does not have a significant effect on firm value due to its internal nature and limited observability. In contrast, green product innovation has a positive and significant effect on firm value, demonstrating that consumer-oriented innovation can enhance market trust and firm valuation.